Analysis of Pangandaran Regency Government’s Performance Accountability Strengthening - Iman Teguh; Abdul Halim (Journal of Accounting and Investment, 2023)
Research aims: This study aims to analyze the Pangandaran Regency Government’s performance accountability strengthening, which took place relatively quickly, and identify performance accountability strengthening plans for the coming period.Design/Methodology/Approach: This research used a qualitative and case study approach to achieve the research objectives. Data collection techniques employed were in-depth interviews and documentation.Research findings: The analysis results showcased that Pangandaran Regency Government’s performance accountability strengthening was dominated by coercive and mimetic isomorphism, but the phenomena move towards normative isomorphism. This study also uncovered that the plan to strengthen performance accountability for the next period formed a specific pattern over time.Theoretical contribution/Originality: This research also provides an academic contribution as a reference regarding performance measurement systems and the institutional isomorphism phenomenon.Practitioner/Policy implication: This research provides a practical contribution to the Pangandaran Regency Government and other local governments that still have professional problems in strengthening performance accountability. Research limitation/Implication: This study has limitations, i.e., in the discussion of the Pangandaran Regency Government’s performance accountability strengthening plan, in which this research had not been accompanied by a review of the Pangandaran Regency Government's Regional Medium Term Development Plan (RPJMD) for 2021-2026. It was because when researchers collected data, the RPJMD was still in preparation.